Pengaruh Profitabilitas, Leverage, dan Kepemilikan Institusional Terhadap Nilai Perusahaan pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Wulan Nuranisya; Adrie Putra (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this study was to analyze the effect of profitability, leverage, and institutional ownership on firm value in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The method used in this research is a causal quantitative approach using secondary data obtained from the Company's annual financial statements published on the IDX. The population in the study was 92 companies and obtained research samples using purposive sampling technique 53 companies from 2020 to 2023, resulting in 212 samples. The results of the study state that the variables of profitability, leverage, and institutional ownership simultaneously have a significant effect on firm value. Partially, profitability has no effect on firm value. Meanwhile, leverage and institutional ownership have a significant effect on firm value.